Q-Vax Q fever vaccine failures, Victoria, Australia 1994–2013. Issue 51 (18th December 2017) - Bond, Katherine A.; Franklin, Lucinda J.; Sutton, Brett; Firestone, Simon M.
Highlights: Retrospective case series of 659 cases of acute Q fever in Victoria Australia, 1993–2013. 34 cases vaccinated with Q-Vax (whole cell formalin inactivated vaccine) prior to symptom onset. 13 of 34 cases represent first case series of Q-Vax vaccine failures >15 days post vaccination. 10 cases positive on Q fever screening precluding vaccination, later developed acute Q fever. Abstract: Q-Vax®, a whole cell formalin inactivated vaccine, is currently the only licensed Q fever vaccine for humans world-wide. Efficacy is high, although vaccine failures have been described for those vaccinated within the incubation of a naturally acquired infection. In Australia, it is widely used to prevent occupational acquisition of Q fever and is the mainstay for outbreak control. A retrospective review of all notified cases of acute Q fever to the Victorian department of health, 1993–2013, revealed 34 of 659 cases were previously vaccinated and 10 cases were positive on pre-vaccination screening, precluding vaccination. Twenty-one cases described high-risk exposures for C. burnetii prior to and within 15 days post vaccination and are likely to have been vaccinated within the incubation period of a natural infection. Thirteen cases described symptom onset more than 15 days post vaccination and thus may represent the first described series of Q-Vax vaccine failures following appropriate vaccination.